The development of a self-help intervention to build social confidence in people living with visible skin conditions or scars: a think-aloud study - Madeline Pasterfield; Sally-Anne Clarke; Andrew R Thompson (SAGE Publishing, 2019)
Introduction: People with a visible difference, such as scarring or a skin condition, can experience anxiety and intrusive reactions from others when in social situations. The use of products to conceal marks on the skin is provided in a number of different hospital services and by charities. However, there are relatively few psychosocial interventions available for these individuals. Objectives: To examine the views of skin camouflage users and practitioners on the acceptability, usability and need for a specifically developed cognitive behavioural therapy (CBT) self-help booklet. Methods: A think-aloud protocol and descriptive form of thematic analysis were used to ascertain participants' views of this novel psychosocial intervention. Nine participants took part in think-aloud interviews that were analysed using thematic analysis. Six skin camouflage users and three skin camouflage practitioners participated in the study. Results: Support for the relevance, acceptability and usability of the booklet was found from both participants who used camouflage and those who provided it. However, some participants reported that they would envisage that some people would need additional support so as to be able to use the techniques described within the booklet. Conclusions: This study represents an important step towards developing a brief self-help intervention for people with living with visible skin conditions or scars and demonstrates the importance of seeking feedback from experts by experience on theoretically informed psychological interventions for this patient group.